Analisis Tingkat Kesehatan pada PT Bank Central Asia Tbk - Rahmah Devi Syahputri; Fatma Dwi Jati; Muhammad Asrin Jazuli (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
Solid financial performance is a crucial foundation for companies to achieve long-term success. In the banking context, financial health assessments are essential, as they directly relate to the stability of the national financial system. Therefore, the Financial Services Authority (OJK) has established standards for evaluating bank soundness using the RGEC method, which includes four key aspects: Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital. This study aims to analyze the soundness level of PT Bank Central Asia Tbk (BCA) during the 2020–2024 period using the RGEC approach. The assessment is conducted by evaluating financial ratios such as Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Good Corporate Governance (GCG), Return on Assets (ROA), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR). The analysis results show that BCA achieved a "very healthy" rating (PK-1) in all RGEC aspects. This reflects BCA's ability to effectively manage risk, implement sound corporate governance principles, and maintain strong profitability and capital. These findings strengthen BCA's position as one of the best-performing banks in Indonesia and demonstrate the company's commitment to maintaining financial stability and customer trust.